2015
DOI: 10.1016/j.cca.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Utility of presepsin (sCD14-ST) as a diagnostic and prognostic marker of sepsis in the emergency department

Abstract: Utility of presepsin (sCD14-ST) as a diagnostic and prognostic marker of sepsis in the emergency department, Clinica Chimica Acta (2015), doi: 10.1016/j.cca.2015.08.013 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
9
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 22 publications
5
62
9
12
Order By: Relevance
“…In addition, the sensitivity and the specificity of the proposed cut-off in relation to the median length of stay observed in our study (17 days) were 85% and 43% respectively. The data obtained seem to demonstrate the role of this biomarker in providing prognostic information also in COVID-19 patients, as already described in several different diseases [3][4][5][6][7], allowing to identify, during the early phase of the monitoring, the patients suffering from a more severe disease which will be hospitalized for a more long time. The elevation of PSP, resulting from a dose-response mechanism of the host-pathogen interaction, occurs in the initial phase of the pathogen recognition, and remains elevated during several days on the basis of the disease severity [13] underlining the additional value of the biomarker in the prognostic assessment of patients [5][6][7]13].…”
Section: To the Editorsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, the sensitivity and the specificity of the proposed cut-off in relation to the median length of stay observed in our study (17 days) were 85% and 43% respectively. The data obtained seem to demonstrate the role of this biomarker in providing prognostic information also in COVID-19 patients, as already described in several different diseases [3][4][5][6][7], allowing to identify, during the early phase of the monitoring, the patients suffering from a more severe disease which will be hospitalized for a more long time. The elevation of PSP, resulting from a dose-response mechanism of the host-pathogen interaction, occurs in the initial phase of the pathogen recognition, and remains elevated during several days on the basis of the disease severity [13] underlining the additional value of the biomarker in the prognostic assessment of patients [5][6][7]13].…”
Section: To the Editorsupporting
confidence: 69%
“…Soluble cluster of differentiation (CD) 14 subtype (sCD14-ST; 64 amino acids, 13 kDa), also termed presepsin (PSP), a small soluble peptide generated from soluble CD14, is known to function as a regulatory factor that can modulates immune responses by interacting with T and B cells [3]. Currently, the results of many clinical studies indicated that PSP is a useful biomarker not only for early diagnosis, but also for risk stratification, and prognosis prediction in sepsis patients as well in patients suffering from pneumonia [4][5][6][7]. In order to verify the potential usefulness of this biomarker in risk stratification of patients (n = 75) suffering from COVID-19 microbiology proven infection (Table 1), PSP measurement in lithium-heparin plasma samples using a chemiluminescent enzyme immunoassay (CLEIA) (Pathfast, Chemical Medience Corporation, Tokyo, Japan), was carried out in addition to routine laboratory tests performed during the period of hospitalization (from January to March 2020) in the intensive care unit (ICU, n = 21, 28%) and/or in infectious disease ward (IW, n = 54, 72%).…”
Section: To the Editormentioning
confidence: 99%
“…On the other hand, presepsin, PCT and CRP levels were increased over 15 days in non-surviving septic patients. Recently, presepsin concentrations were found to show a decreasing tendency from admission to 72 h in septic survivors, whereas in septic non-survivors, the concentrations showed an increasing tendency [40]. Moreover, it has been recently reported that, in septic survivors, presepsin levels seemed to decrease slightly from day 0 to day 7, whereas the PCT and CRP levels at day 7 tended to be much lower than those at day 0.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, 86 studies were included after two updated searches in February 2015 and September 2016 (Fig. 1) (Abidi et al 2008; Ahmadinejad et al 2009; Al-Nawas et al 1996; Anand et al 2015; Balc et al 2003; Barati et al 2010; Battista et al 2016; Bell et al 2003; Beqja-Lika et al 2013; Carpio et al 2015; Castelli et al 2004; Clec’h et al 2006; de Pablo et al 2013; Dorizzi et al 2006; Du et al 2003; Endo et al 2012; Farag et al 2013; Feng et al 2012; Gaini et al 2006; Garnacho-Montero et al 2014; Gerrits et al 2013; Giamarellos-Bourboulis et al 2008; Gibot et al 2004; Godnic et al 2015; Guven et al 2002; Han et al 2016; Harbarth et al 2001; Hoenigl et al 2013; Hou et al 2012, 2016; Hsu et al 2011; Ishikura et al 2014; Ivancevic et al 2008; Jekarl et al 2013, 2014; Jiang et al 2015; Kim and Zhang 2012; Kofoed et al 2007; Latour-Perez et al 2010; Lewis et al 2015; Li et al 2013a; Lin et al 2015; Matera et al 2013; Mat-Nor et al 2016; Mearelli et al 2014; Meynaar et al 2011; Miglietta et al 2015; Miller et al 1999; Muthiah et al 2007, Naeini and Montazerolghaem 2006; Oshita et al 2010; Papadimitriou-Olivgeris et al 2015; Ratzinger et al 2013; Reichsoellner et al 2014; Righi et al 2014; Rivera-Chavez and Minei 2009; Rogina et al 2014; Romualdo et al 2014; Ruiz-Alvarez et al 2009; Sakr et al 2008; Scherpereel et al 2006; Schulte et al 2011; Selberg et al 2000; Seok et al 2012; Shozushima et al 2011; Sierra et al 2004; Su et al 2012, 2013; Sungurtekin et al …”
Section: Resultsmentioning
confidence: 99%